Perbedaan Berat Badan Bayi Usia 0-6 Bulan Yang diberikan Asi Eksklusif dengan Susu Formula - Septi Kurniawati; Rizky Dwiyanti Yunita; Srianingsih Srianingsih (Akademi Kesehatan Rustida, 2021)
Body weight is the most important anthropometric measure used to check the health of children in this age group. Increased baby weight is influenced by several factors such as genetics, gender, nutrition, including breastfeeding. Exclusive breastfeeding will ensure ideal nutrition and prevent the baby from being overweight. On the other hand, giving formula milk to babies less than 6 months has a high risk of being overweight. The harmful impact of formula feeding is that babies are more susceptible to disease. Handling in this study is as a health worker by providing counseling to mothers since pregnancy, the importance of exclusive breastfeeding for newborns up to the age of 0-6 months, and explaining to mothers the benefits and advantages of exclusive breastfeeding. In addition to providing counseling to mothers, providing support to families, especially husbands to support mothers in exclusive breastfeeding for 0-6 months of age. This type of research is analytic research using cross sectional method where this design has a comparison group (control). This study used all infants aged 0-6 months who were given both exclusive breastfeeding and formula milk. This study was analyzed using the Wilcoxon test to determine the weight comparison of infants aged 0-6 months who were given exclusive breastfeeding and formula milk. The results of the Wilcoxon test obtained that the calculated value of Z is greater than Z table of (4.472 > -1.96 the price (-) is not taken into account because the absolute price) then H0 is rejected and H1 is accepted, meaning that the conclusion is that there is a comparison of weight gain of infants given Exclusive Breastfeeding and Formula Milk.